2012
DOI: 10.1016/j.breast.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparity in estrogen receptor positive breast cancer patients receiving trimodality therapy

Abstract: Black women had worse survival outcomes in this cohort. This disparity was driven by (1) a higher proportion of ER- and TN tumors in black women and (2) worse outcome of similarly treated black women with ER+ breast cancer. The underlying causes of racial disparity within hormone receptor categories must be further examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…[26] Other large studies have shown that in those with HR positive breast cancer, survival outcomes among African Americans are significantly worse than Caucasians. [25, 32, 35] An analysis comparing the outcomes of African American with non-African Americans breast cancer patients treated on a large randomized phase III adjuvant trial, reported inferior disease free and overall survival outcomes for HR positive African Americans patients. [32] TNBC patients did not have any differences in outcome by race.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Other large studies have shown that in those with HR positive breast cancer, survival outcomes among African Americans are significantly worse than Caucasians. [25, 32, 35] An analysis comparing the outcomes of African American with non-African Americans breast cancer patients treated on a large randomized phase III adjuvant trial, reported inferior disease free and overall survival outcomes for HR positive African Americans patients. [32] TNBC patients did not have any differences in outcome by race.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in treatment and prognosis, the racial gap in breast cancer death rates has widened, 1,2 with black women having consistently lower survival rates [3][4][5][6][7] and lower disease-specific survival rates in comparison with white women 8,9 ; black women are currently 39% more likely to die of breast cancer than their white counterparts. 10 Multiple studies have reported higher mortality rates for black women at all disease stages, even after adjustments for age, tumor size, nodal status, hormone receptor status, and histology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our findings suggest the role of the ADME gene SLC7A5, a solute carrier (SLC) transporter, in racial disparity in the tamoxifen treatment outcome of breast cancer patients -AA patients exhibited lower sensitivity to tamoxifen than did EA patients [41,42] (Supplementary Figure 7). Our BRCA dataset analysis showed that the E-CpG cg27560818 on SLC7A5 exhibited a significantly lower methylation level in the AA population than that in the EA population.…”
Section: Discussionmentioning
confidence: 88%